The Analysis of Financial Rewards on Employee Engagement in the Public Sector: Cross-Cultural as a Moderating Variables - Mdhlalose, Dickson (International Journal of Business, Law, and Education, 2024)
Cross-cultural research on the influence of individuality and collectivism on employee engagement is lacking. This study aims to analyse the impact of employee financial rewards on employee engagement with a focus on individualistic and collectivistic cultures as moderating variables in a public sector organisation. This research employed standardised face-to-face open-ended interviews. The research instrument is made from one theme and five open-ended questions to address the objectives of this study. The constant comparative data analysis approach was employed in conjunction with content analysis. The researcher categorized the data based on their disparities as well as their similarities. This study found that the municipality offers its employees financial rewards; however, due to inequality, unfairness, favouritism, and political influence, employees are not rewarded fairly, leading to employees being unhappy and disengaged from their work and the organisation. The municipality does not practice either a collectivistic or individualistic culture. A poor imbalance between individualistic and collectivistic cultures reduces the impact of financial rewards on employee engagement. This study's findings emphasise that the effectiveness of financial rewards on employee engagement depends on the organisation's practices and the equilibrium of individualistic and collectivistic cultures.